DIVINE COVENANT IN THE PERSPECTIVE OF THE QUR'AN VERSES - Soysaldi, Haci Mehmet (Ilahiyat Bilimleri Arastirma Vakfi, 2019)
The aims in this study is to examine the divine contract of almighty Allah with His servants in the perspective of Qur'anic verses. First, misak and ahd concepts used for the divine contract in the Qur'an were analyzed. Then, the divine agreements of Allah with his creatures are explained in the light of the Qur'anic verses. The research was concluded by noting the rewards of those who remain faithful to and the penalties to those who violate the divine agreements. God created human and placed ability to know and to believe their creators and His discipline. This is called the divine contract. Indeed, in verse of A'raf 172 God has asked all souls the question Am I not your Lord? and after this question, all the souls replied that Yes you are our Lord, we promise. This is called elest bezmi or bezm-i elest. Some scholars have said that this convention took place in the realms of the souls before people were created and sent to the world. The others say that this divine contract consists of the expression of the faith placed in human nature (fitrat) in a representative language. The vious of God's deed is unknown as the form of His existence. Man can never comprehend the vious of His deeds just as man cannot comprehend the form of His existence. Only Allah knows the truth since this is a metaphysical matter. We do not know entirely and exactly how Allah took the promise from man. It is compulsory to human being to believe that God has taken the promise from man about believing in his existence and oneness. Almighty Allah has placed the ability to every human nature to know Allah and to believe in His discretion. When some people are created and sent to the world, they act according to the necessity of this divine agreement and know Allah and worship him. Some people forget or ignore this divine agreement they deny Allah and turn away from worshiping Allah. Thus, they break down their promises. Almighty Allah reminds people of the divine contract by sending prophets at various times throughout human history and advice to human beings to act according to the divine contract. In short, the prophets invite people to believe in Allah existence and to live in a frame of His commandments by obeying the commands of Allah. Allah has taken the covenant from the prophets, Jews, Christians, idolaters and believers throughout human history. Almighty Allah has taken words from each prophet that they will do the work given to them properly. The prophets must do the divine notification. For this cause, it is necessary to endure difficulties, to make all kinds of material and spiritual sacrifices and even to fight if it is necessary. It is the exam of the prophets to bear these difficulties and to fulfill the task. As a matter of fact, the prophets will be questioned as to whether they had promised to Allah on the Day of Judgment, whether they had announced the commandments revealed to them, and whether people followed these commandments. The prophets will also testify in favor of and against their followers on Day of Judgment. Almighty Allah, had received covenant from the Jews to explain Torah to the people, from the Christians to explain Bible to the people. However, both the Jews and the Christians have altered and altered the divine books that were given to them in exchange for a very little world interest. Almighty Allah, had received covenant from the Jews to explain Torah to the people, from the Christians to explain Bible to the people. However, both the Jews and the Christians have altered and altered the divine books that were given to them in exchange for a very little world interest. Those who break Allah's covenant deserve the curse of God. Almighty Allah says: And those who break the covenant of Allah, after its ratification, and sever that which Allah has commanded to be joined (i.e. they sever the bond of kinship and are not good to their relatives), and work mischief in the land. On them is the curse (i.e. they will be far away from Allah's Mercy), and for them is the unhappy (evir) home (i.e. Hell). (Ar-Ra'd, 13/25) Indeed, the Sons of Israel were subjected to various misfortunes because they breaked their covenant with Allah. And they are cursed by Allah and their hearts are solidified. Thus, those who fail to fulfill His promise to Allah / those who disobey the Scripture receive damages and mischiefs in the world, with their hearts being hardened. Almighty Allah has prepared a great punishment in the Hereafter for those who break Allah's covenant.
Keywords: Tafsir; Qur'an; covenant; testament; contracting; disrupt